2021
DOI: 10.1021/acs.chemrev.1c00371
|View full text |Cite
|
Sign up to set email alerts
|

The Bioinorganic Chemistry of Mammalian Metallothioneins

Abstract: The functions, purposes, and roles of metallothioneins have been the subject of speculations since the discovery of the protein over 60 years ago. This article guides through the history of investigations and resolves multiple contentions by providing new interpretations of the structure-stability-function relationship. It challenges the dogma that the biologically relevant structure of the mammalian proteins is only the one determined by X-ray diffraction and NMR spectroscopy. The terms metallothionein and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
150
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(159 citation statements)
references
References 436 publications
5
150
0
4
Order By: Relevance
“…This and later research demonstrated that MTs are low molecular weight (about 6500 Da varying depending on the metal content), cysteine-rich metal-binding proteins. A wide variety of organisms contain these proteins, including bacteria, fungi and all eukaryotes, i.e., plant and animal species [10,14].…”
Section: Metallothioneins Their Discovery Isolation and Chemical Prop...mentioning
confidence: 99%
See 1 more Smart Citation
“…This and later research demonstrated that MTs are low molecular weight (about 6500 Da varying depending on the metal content), cysteine-rich metal-binding proteins. A wide variety of organisms contain these proteins, including bacteria, fungi and all eukaryotes, i.e., plant and animal species [10,14].…”
Section: Metallothioneins Their Discovery Isolation and Chemical Prop...mentioning
confidence: 99%
“…We have continuously contributed to the knowledge about cadmium toxicology also in the last four decades and the present review and commentary summarizes our findings and gives our views on the role of metallothionein in cadmium toxicology as applied to risk assessment. Other reviews give detailed chemical properties of metallothionein [10] and detailed molecular pathways of importance for Cd kinetics and toxicity [11], not yet fully used in risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc remains in the +2 oxidation state, i.e., Zn 2+ . The cellular availability of zinc(II) ions is controlled by membrane transporters and by release from vesicular stores or from metallothioneins, which are relatively small cysteine sulfur-rich proteins that contain up to seven bound zinc(II) ions and are highly dynamic in their metal binding and regulation [30]. In the process of zinc dissociation from metallothionein, redox reactions do have a role.…”
Section: Cellular Metal Metabolism As a Part Of Metabolic Pathways And Signal Transduction Networkmentioning
confidence: 99%
“…It is also interesting that the discovery of the MTs has been the result of a search for cadmium proteins rather than zinc proteins as a comprehensive review of the 60+ years of research on mammalian MTs summarizes [21]. There are quite a few instances where thiophilic metals in proteins and enzymes can exchange for each other depending on their specific binding constants.…”
Section: The Special Issue On Special Thiophilic Metalsmentioning
confidence: 99%